Fibrosarcomatous pigmented dermatofibrosarcoma protuberans: A case report with review of the literature - ISHIDA, MITSUAKI (D.A. Spandidos, 2012)
Dermatofibrosarcoma protuberans (DFSP) is a relatively rare low-grade sarcoma that occasionally exhibits melanin-containing spindle cells within the tumor. Fibrosarcomatous DFSP (FS-DFSP) is a variant that is characterized by areas which are histopathologically indistinguishable from fibrosarcoma. In the present study, we describe a case of fibrosarcomatous pigmented DFSP and review the clinicopathological features of this extremely rare lesion. A 51-year-old male presented with a slow-growing nodular cutaneous mass in his left upper arm. Histopathologically, the resected tumor was comprised of pigmented DFSP in approximately 20% of the tumor, with the remaining area further covered by a fibrosarcomatous component. A review of the clinicopathological features of the five previously reported cases as well as the present case indicated that this lesion mainly affects middle-aged males and occurs mostly in the extremities. Melanin-containing spindle cells are present only in the conventional DFSP component. The prognosis appears to be poor; in the six cases reviewed, four demonstrated multiple metastases and three succumbed to the disease. Our analyses revealed that the presence of a fibrosarcomatous component in pigmented DFSP is associated with aggressive behavior; therefore, careful assessment for the presence of a fibrosarcomatous component is necessary in the diagnosis of this disease.